2023
DOI: 10.3390/foods12132478
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest Calcium Chloride Treatment Strengthens Cell Wall Structure to Maintain Litchi Fruit Quality

Abstract: Litchi (Litchi chinensis Sonn.) fruit deterioration occurs rapidly after harvest and is characterized by pericarp browning, pulp softening, and decay. In this study, we found that calcium chloride (CaCl2) treatment (5 g L−1 CaCl2 solution vacuum infiltration for 5 min) affected the cell wall component contents and cell wall-degrading enzyme activities of litchi fruit during storage at room temperature. CaCl2 treatment significantly increased the contents of Ca2+ and cellulose, while it decreased the water-solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…However, excessive cytoplasmic Ca 2+ can damage membranes and elevate respiratory rates, leading to increased weight loss, as observed when CaCl 2 concentrations exceeded 1.0%. For example, Guo et al [26] demonstrated that post-harvest treatment of lychee with Ca chloride strengthened the cell wall structure, delaying enzymatic browning of the pericarp, pulp softening, and disease development.…”
Section: Discussionmentioning
confidence: 99%
“…However, excessive cytoplasmic Ca 2+ can damage membranes and elevate respiratory rates, leading to increased weight loss, as observed when CaCl 2 concentrations exceeded 1.0%. For example, Guo et al [26] demonstrated that post-harvest treatment of lychee with Ca chloride strengthened the cell wall structure, delaying enzymatic browning of the pericarp, pulp softening, and disease development.…”
Section: Discussionmentioning
confidence: 99%
“…It extracts and clarifies fruit juices, reduces viscosity, and releases nutrients, a property that has led to its use in improving feed absorption and textile degumming [8]. In previous reports, there have also been many studies on the reduction of PG enzyme activity by post-harvest treatment of fruit to improve fruit quality [9,10].…”
Section: Introductionmentioning
confidence: 99%